2008
DOI: 10.1128/jvi.01050-08
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering of the Prehairpin Intermediate of gp41 by Peptide N36 Mut(e,g) Potentiates the Human Immunodeficiency Virus Type 1 Neutralizing Activity of Monoclonal Antibodies Directed against the N-Terminal Helical Repeat of gp41

Abstract: Mut(e,g) exhibits the same effects on the broadly neutralizing 2F5 and 4E10 monoclonal antibodies directed against the membrane-proximal extended region of gp41. The mechanistic implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 56 publications
(76 reference statements)
3
35
1
Order By: Relevance
“…To assess the relevance of epitope exposure on HIV-1 neutralization, we compared the lifetime of 2F5 mAb neutralization of wild-type and L669S mutant pseudotyped viruses. The exposure during the fusion process of MPER neutralizing epitopes to MPER mAbs (2F5, 4E10) and gp41 entry inhibitor peptides has previously been estimated as 15-20 min (11,(25)(26)(27)(28). We hypothesized that the L669S mutation could alter the MPER structure such that gp41 neutralizing epitopes are exposed for even longer.…”
Section: L669s Mutation Prolongs the Temporal Window Of 2f5 Mabmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the relevance of epitope exposure on HIV-1 neutralization, we compared the lifetime of 2F5 mAb neutralization of wild-type and L669S mutant pseudotyped viruses. The exposure during the fusion process of MPER neutralizing epitopes to MPER mAbs (2F5, 4E10) and gp41 entry inhibitor peptides has previously been estimated as 15-20 min (11,(25)(26)(27)(28). We hypothesized that the L669S mutation could alter the MPER structure such that gp41 neutralizing epitopes are exposed for even longer.…”
Section: L669s Mutation Prolongs the Temporal Window Of 2f5 Mabmentioning
confidence: 99%
“…The extended window of opportunity for the MPER mAbs to sample the optimal conformation for binding could explain the observed hypersensitivity of L669S mutant pseudotyped virus. Using a virus-cell postattachment neutralization assay (25), viral infectivity as a function of time of addition of 2F5 mAb was measured for the WT Env pseudotyped virus (TND_669L) and L669S mutant Env pseudotyped virus (TND_669S). We observed that the lifetime of 2F5 neutralization was ∼3-fold longer for the TND_669S pseudotyped virus (t 1/2 = 45.1) when compared with TND_669L pseudotyped virus (t 1/2 = 14.5 min) (Fig.…”
Section: L669s Mutation Prolongs the Temporal Window Of 2f5 Mabmentioning
confidence: 99%
“…This FcR-mediated restriction of lentiviruses also appeared to involve the induction of the cyclin-dependent kinase inhibitor p21 Cip1/WAF1 . It is unlikely that a similar mechanism may be responsible for the efficient neutralization of HIV by MPER MAbs because this phenomenon does not occur with every immune complex, as was observed in the FcR-mediated restriction of lentiviruses in macrophages (20).A more likely mechanism for enhanced Ab-mediated neutralization of HIV-1 in TZM-bl/Fc␥RI cells is that the Fc receptor pre-positions Abs at the virus surface, thereby breaching the steric barrier at the virus-cell interface (21) for Abs whose epitopes are not fully revealed until the Env glycoprotein spike changes con- [22][23][24][25]. We note that CD89 (Fc␣R1) expression on TZM-bl cells does not potentiate the neutralizing capacity of the IgA version of 2F5 (our unpublished results).…”
mentioning
confidence: 99%
“…A more likely mechanism for enhanced Ab-mediated neutralization of HIV-1 in TZM-bl/Fc␥RI cells is that the Fc receptor pre-positions Abs at the virus surface, thereby breaching the steric barrier at the virus-cell interface (21) for Abs whose epitopes are not fully revealed until the Env glycoprotein spike changes con- [22][23][24][25]. We note that CD89 (Fc␣R1) expression on TZM-bl cells does not potentiate the neutralizing capacity of the IgA version of 2F5 (our unpublished results).…”
mentioning
confidence: 99%
“…Various evidences have been interpreted to indicate that the MPER epitopes are exposed or formed in the CD4-liganded Env spike but are not present, or are only minimally present, on the unliganded spike, leaving a relatively narrow window of opportunity for MAb binding and neutralization (2,6,16,24,31,82). A two-step model has been proposed in which 4E10 and 2F5 MAbs bind to, and diffuse within, the plane of the membrane prepositioning these MAbs for efficient interaction with the membrane-associated exposure/creation of the cognate epitopes upon CD4-induced Env spike triggering (1,2).…”
mentioning
confidence: 99%